2017
DOI: 10.14202/vetworld.2017.924-926
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening for hemotropic mycoplasmas in captive Barbary sheep (Ammotragus lervia) in southern Brazil

Abstract: Aim:This study is part of an active surveillance program for monitoring animal health status in endangered species, and was conducted to screen captive Barbary sheep (Ammotragus lervia) for hemoplasma infection.Materials and Methods:A total of 12 blood samples were collected, DNA extracted and further tested by a pan-hemoplasma polymerase chain reaction protocol.Results:Animals were clinically healthy and not infested by ectoparasites. Although housekeeping gene DNA was successfully amplified, all the Barbary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In some studies with larger sample sizes, as many as 89% of white-tailed deer (Odocoileus virginianus) and 72% of marsh deer (Blastocerus dichotomus) (Grazziotin, Duarte, et al, 2011) were infected. Three studies failed to detect haemoplasmas in ungulates, all of which sampled captive populations: one study included a very small sample of Barbary sheep (Ammotragus lervia) (Santos et al, 2017), whereas the other two sampled peccaries (Tayassu spp.) (da Costa Dias et al, 2019).…”
Section: Artiodactylsmentioning
confidence: 99%
“…In some studies with larger sample sizes, as many as 89% of white-tailed deer (Odocoileus virginianus) and 72% of marsh deer (Blastocerus dichotomus) (Grazziotin, Duarte, et al, 2011) were infected. Three studies failed to detect haemoplasmas in ungulates, all of which sampled captive populations: one study included a very small sample of Barbary sheep (Ammotragus lervia) (Santos et al, 2017), whereas the other two sampled peccaries (Tayassu spp.) (da Costa Dias et al, 2019).…”
Section: Artiodactylsmentioning
confidence: 99%
“…The dilated pupil observed among zoo monkeys compared to wild monkeys reflects higher sympathetic activity, 24,28 which may be due to captivity-related stress. [30][31][32] Despite the best welfare measures adopted, nothing can fully replace a natural habitat, hence several studies have reported stress among captive exotic animals. [30][31][32] Furthermore, the reliability of pupil diameter as a reflection of autonomic system activity ( Figure 2) and mental stress has previously been demonstrated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Despite the best welfare measures adopted, nothing can fully replace a natural habitat, hence several studies have reported stress among captive exotic animals. [30][31][32] Furthermore, the reliability of pupil diameter as a reflection of autonomic system activity ( Figure 2) and mental stress has previously been demonstrated in humans. 3,5,[24][25]27,33 The feasibility to non-invasively and objectively quantify stress based on iris/pupil area ratio in our opinion has potential to be of utility in personalised animal welfare measures.…”
Section: Discussionmentioning
confidence: 99%